PEDAGOGICAL PARADIGM SHIFT IN WRITING: IMPLICATIONS FOR CLASSROOM APPLICATION - Adegbile, J. A.; Alabi, O. F. (Sokoto Educational Review, 2020)
Instruction in writing has moved from a product orientation to process orientation. The development which started in America in the early 1960s initially commenced with the 4 but later got introduced to the 42. in Nigeria various research findings have identified the. effectiveness of process pedagogy. In spite o these findings, teachers of English have stuck to product-oriented approach. Teachers, probably, are not aware of the pedagogical paradigm shift in writing or perhaps lack the knowledge of were to intervene in learners’ writing process or how to go about it. In this paper, the effort is made to explain this pedagogical paradigm shift and its implications for both teachers and learners. The attempt is equally made to intimate teachers with the various stages in the writing process and where and how they can intervene to help the learners.